Moral Reasoning Development and its Relationship to Eudemonic Well-Being and Positive Social Behavior - Migdady, Yusef (Jordan Journal of Educational Sciences, 2015)
This study aimed to identify the Moral Reasoning of all the Eudemonic Well-Being of Positive Social Behavior. A random sample of 237 students was selected from the undergraduates in the College of Education at Al-Baha University, Saudi Arabia. To achieve the objectives of the study, the researcher used the Moral Reasoning Development scale, Eudemonic Well-Being, and the measure of Positive Social Behavior. the validity and reliability of the scales are confirmed. The results showed that the Moral Reasoning Development, the level of Eudemonic Well-Being, and the level of Positive Social Behavior were moderate. Also, the results showed a statistically significant correlation between the Moral Reasoning Development and Eudemonic Well-Being level